Simulation studies of mole drain characteristics - Mishra, A K; Sarkar, T K; Bhattacharya, A K (Journal of Agricultural Engineering, 2000)
A laboratory study was carried out to assess the suitability of clay soils for moling and to evaluate the performance of mole drains constructed under wide variety of initial soil moisture and bulk density conditions by simulating the field situations in a Hale-Shaw model. The soil properties at the time of construction of mole channels significantly affected the performance of mole drains, channel stability, development of cracks and fissures and the force required for moling. At an initial soil moisture content of 20 per cent (v/v) and bulk density of 1.4 g/cmÂ³ the drainage performance was quite satisfactory. At low density (1.25 g/cmÂ³) it was difficult to construct the mole channels due to too loose packing. Also, deformation in mole shapes were predominant when the same were subjected to saturation. At higher moisture content no major cracks and fissures developed to act as the secondary channels for carrying water to the mole drains.